2023
DOI: 10.1007/s10570-023-05491-3
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and pro-wound healing properties of microporous cellulosic sponge from Gleditsia triacanthos pods functionalized with Phytolacca americana fruit extract

Ioana Cristina Marinas,
Gratiela Gradisteanu Pircalabioru,
Eliza Oprea
et al.

Abstract: This study aimed to exploit two invasive plant species to develop a novel, multifunctional, bioactive wound dressing based on a microporous cellulosic sponge (CS) from Gleditsia triacanthos pods and functionalizing them with Phytolacca americana fruit extract. The CS was functionalized, lyophilized, and characterized by Attenuated total reflectance–Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, contact angle, water absorption, and retention capacity. In addition, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…Previous studies and research [17,18] have demonstrated that a high content of anthocyanins and total phenols can be found in compounds extracted from Arundo donax, Tradescantia fluminensis, and Eucalyptus globulus. Additionally, other studies [40,41] have shown that Phytolacca americana, beyond the toxicity of its fruits, exhibits anticancer, antioxidant, and antimicrobial properties. The papers produced from this raw material were analyzed using the JEOL 6100 electron microscope located at the CACTI (Scientific and Technical Research Assistance Center) of the University of Vigo, on the As Lagoas campus in Vigo.…”
Section: Chemical Composition Of Mattermentioning
confidence: 99%
“…Previous studies and research [17,18] have demonstrated that a high content of anthocyanins and total phenols can be found in compounds extracted from Arundo donax, Tradescantia fluminensis, and Eucalyptus globulus. Additionally, other studies [40,41] have shown that Phytolacca americana, beyond the toxicity of its fruits, exhibits anticancer, antioxidant, and antimicrobial properties. The papers produced from this raw material were analyzed using the JEOL 6100 electron microscope located at the CACTI (Scientific and Technical Research Assistance Center) of the University of Vigo, on the As Lagoas campus in Vigo.…”
Section: Chemical Composition Of Mattermentioning
confidence: 99%